Nanoparticles delivery to cancer: Approaches and limitation - Hassan Tamam; Jelan A. Abdel-Aleem; Sayed I. Abdelrahman; Aly A. Abdelrahman (IJRDO-Journal of Applied Science, 2019)
Nanoparticles have received attention as promising delivery system of chemotherapy for cancer treatment. There are many mechanisms through which nanoparticles reaches the tumor site. Many nanoparticles delivery systems have been developed to solve problems associated with chemotherapeutic drugs such as solubility and stability or to increase tumor site specificity as by attachment of ligand to surface of nanoparticles. We provide a critical review about the factors affecting the delivery of nanoparticles to tumor site, mechanisms by which nanoparticles reach the tumor site, types of nanoparticles and limitation of nanomedicine.